Pirolisis Gelombang Mikro Biomassa Tandan Kosong Kelapa Sawit (TKKS): Pengaruh Massa Absorber KOH dan Katalis Zeolit Alam terhadap Energi Produk - Megaprastio, Bayu; Saptoadi, Harwin; Putra, Robertus Dimas Dewangga (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to investigate the effect of the KOH/TKKS ratio on the energy content and composition of three-phase pyrolysis products, with a fixed zeolite mass of 10 g. The pyrolysis process was conducted using 100 g of empty fruit bunches (TKKS) at 450 °C with a residence time of 15 minutes. The evaluation covered pyrolysis performance (yields of biochar, bio-oil, and gas), biochar properties (proximate analysis and energy content), bio-oil (energy content), and gas (composition via GC-TCD and energy content). The results show that increasing the KOH ratio accelerated the attainment of the target temperature from approximately 17 minutes (ratio 2:4) to 10 minutes (ratio 4:4) and promoted a higher gas fraction while reducing the bio-oil yield. The optimal condition for bio-oil production was achieved at a KOH/TKKS ratio of 2:4, yielding the highest bio-oil fraction of 29.3%. A higher KOH mass also increased the concentrations of CO, CO₂, and H₂ in the gas phase while decreasing the fixed carbon content in the biochar. The energy input during pyrolysis decreased significantly from 1513.11 kJ at the 2:4 KOH/TKKS ratio to 813.8 kJ at the 4:4 ratio, primarily due to the accelerated heating rate induced by higher KOH content. Despite this, the 2:4 ratio exhibited the highest energy conversion efficiency, as it produced the largest yield and energy content of bio-oil, contributing to a higher total energy output. These findings highlight the critical role of an appropriate KOH ratio in optimizing product distribution and energy efficiency in the pyrolysis process. The results underscore the potential of TKKS as a renewable energy source through microwave-assisted pyrolysis.